Bio-geochemical simulation for solute transport in Piyungan landfill, Yogyakarta Special Province, Indonesia - Keophousone Phonhalath; Dwikorita Karnawati; Heru Hendrayana; Doni Prakasa Eka Putra; Kenji Jinno (Journal of Applied Geology, 2015)
Piyungan Landfill is the largest in Bantul Regency. According to water quality sampling taken from a leachate pond, there are significant contaminant issues resulting from landfill leachate. The objectives of this research were achieved by applying a two-dimensional bacteria mediated reduction numerical model was applied. Method of characteristic was applied to solve the advection part of the solute transport equation. Three bacteria (X1, X2, and X3) groups were defined in the redox model. In the conceptual model, bacterial X1 utilizes oxygen under aerobic conditions and nitrate, NO-3 under aerobic conditions as electron acceptors. Consequently, under aerobic conditions bacteria X2, and X3 utilize MnO2, and Fe(OH)3 respectively as electron acceptors. In the redox model organic carbon which was defined as CH2O was considered as the electron donor for all bacteria mediated reduction reactions. The results of research are to improve the understanding of biogeochemical processes in aquifer.